Integrated microRNA-mRNA analysis reveals a possible molecular mechanism of enteritis susceptibility in Litopenaeus vannamei. Issue 136 (May 2023) - Fu, Chunpeng; Fu, Xiaopeng; Li, Fajun; Li, Zongzhen; Wang, Aili; Jiang, ShanShan; Liu, Chunqiao; Wang, Hui
Abstract: Enteritis is one of the main diseases affecting Pacific whiteleg shrimp ( Litopenaeus vannamei ) in recent years, and it has resulted in huge losses to the aquaculture industry. Prior to this study, the molecular mechanism underlying enteritis in L. vannamei was unclear, and comprehensive multi-omics analysis had not been conducted. In this study, 1209 differentially expressed genes (DEGs) were identified from the hepatopancreas of L. vannamei with and without enteritis. Kyoto Encyclopedia of Genes and Genomes analysis showed that genes were significantly enriched in immune, metabolic, and endocrine regulatory pathways. Forty-eight significantly different microRNAs (miRNAs) were identified in the miRNA-Seq analysis. Further functional annotation analysis showed that the regulatory pathway of target gene enrichment of differentially expressed miRNAs was consistent with DEGs. Through miRNA-mRNA integration analysis, 47 meaningful miRNA-mRNA pairs were obtained, of which melanogenesis and pancreatic secretion were considered key pathways. Subsequent miRNA-mRNA interaction network analysis revealed that mja-miR-6493-3p, Mja-miR-6494, novel-198, novel-272, novel-261, novel-200, novel-183, novel-184, novel-237, and novel-192 may be key miRNAs involved in the regulation of these two signaling pathways. Finally, the RAS signaling pathway was found to inhibit the translation level of proteins in the hepatopancreas. These results suggest that target gene integration analysis of mRNA-miRNA can reveal the molecular mechanism underlying enteritis in L. vannamei and also provide valuable new insights for resisting enteritis. Highlights: In the enteritis group, the abundance of 1209 DEGs in the hepatopancreas was significantly changed. Differential expression study revealed the up-regulation of 14 miRNAs and down-regulation of 34 miRNAs. Mja-mi R-6494 may lead to a decrease in melatonin immune function due to adaptation to low temperature stimulation. MiR-6494 regulates the expression of up to eight mRNAs associated with digestive enzymes and membrane ion channel proteins. The decrease of RASA1 gene abundance leads to the decrease of translation levels of immune proteins and enzymes.